KONTRAK PENDASAR SYER KEANGGOTAAN KOPERASI: SATU ANALISIS DARI PERSPEKTIF SYARIAH: The Underlying Contract For Cooperative Membership Shares: An Analysis From The Shariah Perspective - Muhammad Fathi; Noordin, Kamaruzaman; Mansor, Fadillah (Online Journal of Islamic Management and Finance (OJIMF), 2025)
This study explores and analyzes the application of Shariah contracts specifically musyarakah and mudarabah in cooperative institutions in Malaysia. It aims to determine the takyif fiqhi for the implementation of membership shares based on cooperative operations in line with the Cooperative Act 1993 and the latest guidelines. Unlike previous studies that focus on conceptual discussions, this study assesses the suitability of Shariah contracts within cooperative membership structures by analyzing legal frameworks and regulatory guidelines in Malaysia. This study adopts a qualitative approach through document analysis of the legal framework governing cooperatives, Shariah contract guidelines, and fiqh texts to evaluate the compatibility of these contracts in cooperative membership structures. Findings reveal that musyarakah, particularly syirkah al-‘inan, is the most suitable contract for membership shares as it aligns with most cooperative regulations. In contrast, mudarabah is less suitable due to conflicts with cooperative principles, particularly shared ownership and active member participation. Despite this, challenges remain in inheritance management of membership shares and dividend distribution, requiring further refinement. This study contributes to the development of a Shariah-compliant framework for cooperative membership shares and serves as a reference for policymakers, cooperative managers, and Islamic finance researchers in improving Shariah compliance in cooperative operations.